Cellular signal transduction in toxicology and pharmacology : data collection, analysis, and interpretation - Boyd, Jonathan W., 1975-; Neubig, Richard R. (Wiley, 2019)
Covering a key topic due to growing research into the role of signaling mechanisms in toxicology, this book focuses on practical approaches for informatics, big data, and complex data sets. Combines fundamentals / basics with experimental applications that can help those involved in preclinical drug studies and translational research Includes detailed presentations of study methodology and data collection, analysis, and interpretation Discusses tools like experimental design, sample handling, analytical measurement techniques